Sunitinib for patients with metastatic non-clear cell renal cell carcinoma: a Multicenter Retrospective Turkish Oncology Group trial - (:unkn) unknown (My University, 2014)
AIM: This study aimed to assess the clinical efficacy and toxicity of sunitinib, a targeted-agent, for non-clear cell renal cell carcinoma. PATIENTS AND METHODS: Sixty-three patients with complete clinical data from 13 oncology Centers were retrospectively evaluated. Outcomes analyzed were objective response rate (ORR), progression-free survival (PFS), overall survival (OS) and adverse events. RESULTS: The median age of all patients, 38 men (60.3%) and 25 women (39.7%), was 63 years (range=25-82 years). Histological subtypes included 46 (88%) cases of papillary RCC, 10 of chromophobe, and 7 unclassified cases. Median treatment duration was seven months (range=2-86 months). At the time of this analysis, 52 patients had discontinued treatment, 33 of whom had died. Treatment discontinuation was due to disease progression in 43 patients, and toxicity in nine. Dose interruption was necessary in 22 (34.9%) patients, and dose reduction in 27 (42.9%). The objective response rate and disease control rate were 11.1% and 63.5%, respectively. The median PFS and OS were 7.6 months (95% confidence interval (CI)=5.5-9.7 months) and 22.0 months (95% CI=13.4-30.6 months), respectively, with 1-year rates of 64.7% and 33.7%, respectively. CONCLUSION: Clinical outcome of the metastatic non-clear cell RCC patients with sunitinib treatment seemed to be worse than the historical data of clear cell RCC patients, in terms of PFS, OS and objective response. New and more effective targeted-therapies and better understanding of the underlying molecular processes are necessary to improve survival outcome for these patients.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Aged, 80 and over; Male; Retrospective Studies; Antineoplastic Agents; Indoles; Carcinoma, Renal Cell; Kidney Neoplasms; Pyrroles; Sunitinib; Adverse effects; metastatic non-clear cell renal cell carcinoma; sunitinib